2015
DOI: 10.1111/pops.12304
|View full text |Cite
|
Sign up to set email alerts
|

Are Conservatives Really More Simple‐Minded than Liberals? The Domain Specificity of Complex Thinking

Abstract: Prior research suggests that liberals are more complex than conservatives. However, it may be that liberals are not more complex in general, but rather only more complex on certain topic domains (while conservatives are more complex in other domains). Four studies (comprised of over 2,500 participants) evaluated this idea. Study 1 involves the domain specificity of a self-report questionnaire related to complexity (dogmatism). By making only small adjustments to a popularly used dogmatism scale, results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 50 publications
(108 reference statements)
2
108
2
1
Order By: Relevance
“…The idea is that ideological differences can and do emerge when using a limited range of stimuli, but when using a broader array of stimuli that are more likely to represent the range of stimuli people experience, these differences disappear (e.g., Brandt et al, 2014;Brandt & Wagemans, in press;Conway et al, 2016;Crawford, 2012;Morgan, Mullen, & Skitka, 2010). For example, sometimes it appears that conservatives are more prejudiced than liberals, but when using a broad range of groups, it's clear that both liberals and conservatives express similar levels of prejudice toward worldview-violating groups .…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The idea is that ideological differences can and do emerge when using a limited range of stimuli, but when using a broader array of stimuli that are more likely to represent the range of stimuli people experience, these differences disappear (e.g., Brandt et al, 2014;Brandt & Wagemans, in press;Conway et al, 2016;Crawford, 2012;Morgan, Mullen, & Skitka, 2010). For example, sometimes it appears that conservatives are more prejudiced than liberals, but when using a broad range of groups, it's clear that both liberals and conservatives express similar levels of prejudice toward worldview-violating groups .…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Research in this area has also garnered some legitimate criticism on scientific grounds. Some of the more thoughtful questions and criticisms have come from members of ISPP, including the following: 1)What about rigidity of the left, especially in Central/Eastern Europe, given its history of dogmatic leadership and totalitarian socialism (Golec de Zavala, & Van Bergh, ; Greenberg & Jonas, )? 2)Are needs to reduce uncertainty and threat associated with authoritarianism—or ideological extremism in general—rather than political conservatism per se (Crowson, Thoma, & Hestevold, ; Greenberg & Jonas, ; van Prooijen, Krouwel, Boiten, & Eendebak, )? 3)Aren't the psychological correlates of social versus economic conservatism very different from one another (Crowson, ; Feldman & Johnston, ; Malka, Soto, Inzlicht, & Lelkes, )? 4)Could it be that the “true” effect sizes between psychological and political variables are much weaker than Jost et al () suggested (Jussim et al, ; Van Hiel et al, )? 5)Aren't ideological differences confined to subjective, self‐report measures that mean little when it comes to actual behavior (Kahan, ; Van Hiel et al, )? 6)Aren't liberals just as biased as conservatives when it comes to motivated social cognition (Conway et al, ; Crawford, ; Kahan, ), and just as prejudiced, too (Brandt, Reyna, Chambers, Crawford, & Wetherell, ; Chambers, Schlenker, & Collisson, )? …”
Section: Political Ideology As Motivated Social Cognitionmentioning
confidence: 99%
“…For instance, some research has shown that religious fundamentalists are not necessarily low in integrative complexity of thought in general, but only with respect to the religious/existential and the moral domains (Pancer, Jackson, Hunsberger, Pratt, & Lea, 1995). Similarly, Conway et al (2016) recently found that conservatives are not necessarily simple-minded across all life domains: while liberals show higher complexity in certain domains (e.g., premarital sexuality, alcohol consumption, abortion), conservatives demonstrate higher complexity in other domains (e.g., death penalty, open-door immigration, loud music). We investigated this question by focusing on the construct of existential quest .…”
Section: Socio-cognitive Characteristics: Low Flexibilitymentioning
confidence: 92%